Application of human platelet lysate in chondrocyte expansion promotes chondrogenic phenotype and slows senescence progression via BMP–TAK1–p38 pathway - Narong Chitchongyingcharoen; Tulyapruek Tawonsawatruk; Jitrada Phetfong; Wrattya Aroontanee; Aungkura Supokawej (Scientific Reports, 2023)
Abstract Osteoarthritis (OA) is one of the most common musculoskeletal degenerative. OA treatments are aiming to slow down disease progression; however, lack of cartilage regeneration efficacy. Autologous chondrocyte implantation (ACI) is a promising cartilage-regeneration strategy that uses human articular chondrocytes (HACs) as cellular materials. However, the unreadiness of HACs from prolonged expansion, cellular senescence, and chondrogenic dedifferentiation occurred during conventional expansion, thus, minimizing the clinical efficacy of ACI. We aimed to examine the effects of a human platelet lysate (HPL) as an alternative human-derived HAC medium supplement to overcome the limitations of conventional expansion, and to explain the mechanism underlying the effects of HPL. During passages 2–4 (P2-P4), HPL significantly increased HAC proliferation capacities and upregulated chondrogenic markers. Simultaneously, HPL significantly reduced HAC senescence compared with conventional condition. HACs treated with LDN193189 exhibited a reduction in proliferation capacity and chondrogenic marker expression, whereas the HAC senescence increased slightly. These findings indicated involvement of BMP-2 signaling transduction in the growth-assistive, anti-senescent, and chondrogenic-inductive properties of HPL, which demonstrated its beneficial effects for application as HAC medium supplement to overcome current expansion limitations. Finally, our findings support the roles of platelets in platelet-rich plasma as a promising treatment for patients with OA.